Modelling drivers of Koha open source library system using partial least squares structural equation modelling - Zainab, A.M.; Kiran, K.; Ramayah, T.; Karim, N.H.A. (Malaysian Journal of Library and Information Science, 2019)
Open source library systems are markedly a less expensive alternative to licensed library systems, but the uptake by libraries in the developing countries has been slower than expected. Focusing on the user, this study employs a human behavior analysis approach to ascertain what factors drive librarians to accept an open source library information system, specifically the Koha library system. This exploratory study is guided by two important components of technology acceptance, the Unified Theory of Acceptance and Use of Technology and the User Acceptance Test. Using a survey questionnaire, data was collected from 245 librarians from five public and private university libraries and analyzed using the PLS-SEM method. Librarians’ attitude towards using technology and social influence are the key determinants of open source library system acceptance. At the same time, system quality and information quality are also two other significant predictors of librarians’ acceptance of open source technology. This study is the first to conceptually integrate technology acceptance predictors and open system success indicators, as used in user acceptance tests, to understand open source library system acceptance and use among university librarians. The identified major predictors can be used by library management to devise strategies to improve librarians’ involvement and use of open source systems.